Underpricing Anomalies: A Study of Companies that IPO on the Indonesian Stock Exchange - Hadi, Hasna; Atikah, Siti (PT FORMOSA CENDEKIA GLOBAL, 2024)
During Initial Public Offerings (IPO), one of the most common anomalies associated with pricing is short-term underpricing. The main objective of this study is to contribute to previous academic research by examining the existing underpricing of companies that conducted Initial Public Offerings (IPO) on the Indonesia Stock Exchange during 2022. With this objective, 58 companies that conducted Initial Public Offerings (IPO) on the Indonesia Stock Exchange during 2022 were examined. This research is a causal associative research with a quantitative approach. In the analysis, the period of this study takes a relatively short-term period, namely the first day and the first seven days. Hypotheses were tested using non-parametric statistical testing methods, namely the Kruskal Wallis test. The empirical findings in this study are that when viewed from the abnormal/adjusted return shows that there is a short-term underpricing anomaly. This means that investors can get abnormal returns by buying the IPO shares. However, when viewed from the cumulative value, it shows that there is no short-term underpricing anomaly in companies conducting Initial Public Offerings (IPO) on the Indonesia Stock Exchange during 2022.